2016
DOI: 10.3748/wjg.v22.i9.2678
|View full text |Cite
|
Sign up to set email alerts
|

Key players in pancreatic cancer-stroma interaction: Cancer-associated fibroblasts, endothelial and inflammatory cells

Abstract: Pancreatic cancer (PC) is the most aggressive type of common cancers, and in 2014, nearly 40000 patients died from the disease in the United States. Pancreatic ductal adenocarcinoma, which accounts for the majority of PC cases, is characterized by an intense stromal desmoplastic reaction surrounding the cancer cells. Cancer-associated fibroblasts (CAFs) are the main effector cells in the desmoplastic reaction, and pancreatic stellate cells are the most important source of CAFs. However, other important compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
142
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(154 citation statements)
references
References 218 publications
2
142
0
1
Order By: Relevance
“…Tumors typically contain a number of different stromal cell types, including fibroblasts, lymphocytes, macrophages and endothelial cells (see Figure 1) [1][2][3][4][5]. In some tumor types (e.g., pancreatic ductural adenocarcinoma [PDAC]), the number and mass of stromal cells in a tumor far exceeds that of the cancer cells [6,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tumors typically contain a number of different stromal cell types, including fibroblasts, lymphocytes, macrophages and endothelial cells (see Figure 1) [1][2][3][4][5]. In some tumor types (e.g., pancreatic ductural adenocarcinoma [PDAC]), the number and mass of stromal cells in a tumor far exceeds that of the cancer cells [6,7].…”
mentioning
confidence: 99%
“…These immune cells maintain the tumor microenvironment in a chronically inflammatory and immunosuppressive state [14]. Endothelial cells are recruited to form new blood vessels in the tumor by secretion of VEGF and other ligands from tumor cells and other cell types [4].…”
mentioning
confidence: 99%
“…Recent reports have suggested that targeting components of the desmoplastic reaction may enhance the activity of therapeutics targeting tumor cells (10,11). CAFs are the main effector cells in the desmoplastic reaction, pancreatic stellate cells being the most important source of CAFs (12). The lack of effective therapeutic options and the consequent high mortality rate of PDAC indicate the need to explore other treatment options, such as those aimed at reducing desmoplasia.…”
mentioning
confidence: 99%
“…Bohaté desmoplastické stroma předsta-vuje jednu ze základních charakteristik duktálního karcinomu pankreatu a řada studií potvrzuje, že role aktivovaného stromálního mikroprostředí má zásadní vliv na agresivitu tumoru a jeho odpověď na terapii [35,36]. Příznivý prognostický význam vysoké denzity TIL byl demonstrován pro několik jejich podtypů, především CD4+, CD8+ T lymfocyty a M1 intratumorální makrofágy [37].…”
Section: Pankreasunclassified